2018
DOI: 10.1002/nau.23592
|View full text |Cite
|
Sign up to set email alerts
|

Mouse urothelial genes associated with voiding behavior changes after ovariectomy and bladder lipopolysaccharide exposure

Abstract: OVX mice persisted with increased voiding frequency after LPS. Urothelial genes that could mediate this voiding behavior include IL6, COX-2, and S-adenosylmethionine decarboxylase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The decrease in bladder weight has also been observed in previous ovariectomy rat and rabbit models, and the reasons may be related to muscle atrophy and collagen fiber substitution [21][22][23][24]. Although this study did not deeply investigate the bladder function, the susceptibility to OAB and UTI caused by the ovariectomy animal model has been widely confirmed [7,[25][26][27]. It is well-known that estrogen receptors are widely distributed in the bladder [28], and obviously, estrogen can to some extent regulate bladder function.…”
Section: Discussionmentioning
confidence: 62%
“…The decrease in bladder weight has also been observed in previous ovariectomy rat and rabbit models, and the reasons may be related to muscle atrophy and collagen fiber substitution [21][22][23][24]. Although this study did not deeply investigate the bladder function, the susceptibility to OAB and UTI caused by the ovariectomy animal model has been widely confirmed [7,[25][26][27]. It is well-known that estrogen receptors are widely distributed in the bladder [28], and obviously, estrogen can to some extent regulate bladder function.…”
Section: Discussionmentioning
confidence: 62%
“…The VSA has been used to accurately predict increased frequency with chemical cystitis and with age (44). It has been used to identify the impact of sex hormones on voiding function (1,35). It has been used to identify a diet-induced physiological change in voiding behaviors (confirmed by cystometry) (26,48).…”
Section: Technical Aspects For Performing Vsamentioning
confidence: 99%
“…Urine profiles of pterin compounds have the potential to become predictive biomarkers of bladder cancer (10). Moreover, Acevedo-Alavarez and colleagues (11) reported that mouse urothelial transcripts of Gch1 might play an important role in modulating voiding behavior changes.…”
Section: Introductionmentioning
confidence: 99%